IMPACTS ON MARITIME TRADE WITH REGARD TO NAVIGATIONAL ROUTE ADJUSTMENTS IN AVOIDING CONFLICTS WITH MARINE PROTECTED AREAS: AN INSIGHT TO THE LAW AND POLICY - Gunasekera, Dan Malika (UI Scholars Hub, 2017)
Establishing a Marine Protected Area (MPA) in a State’s maritime jurisdiction is a concept that became a much of practical approach alongside IUCN’s (International Union for Conservation of Nature) efforts for the protection of maritime environment. Although, the 3rd United Nations’ Conference on Law of the Sea (UNCLOS III) emphasized the importance of protecting seas and oceans as a State’s duty within its role as a custodian, this conceptual framework has not been well laid upon on its Members States beyond the conventional provisions enumerated in its entirety, and in Article 194.5 in particular. However, later development of the subject has alarmed the international community to a critical juncture where they have felt the importance of establishing MPAs in most sensitive sea areas by 2012. It is a well-known fact that shipping contributes heavily on issues pertaining to marine pollution in coastal waters though it is not the main cause taking into consideration of land-based sources. Nevertheless, shipping does contribute a considerable degree of hazard to living and non-living resources of the seas, especially considering its effects on endangered fish stocks. Unlike in the case of a global initiative, number of regional and unilateral means of proclaiming MPAs has taken place while enacting remarkable policies in the Mediterranean, Baltic, and North Sea areas as evident. In particular, Lord Donaldson’s Report in recommending Safer Ships, Cleaner Seas within the United Kingdom’s so-called MEHRA (Marine Environmental High Risk Areas) policy has brought into limelight some important steps that need to put in place with the use of the seas for shipping activities while appreciating IMO’s (International Maritime Organization) Resolution A.982(24) guidelines pertaining to Particularly Sensitive Sea Areas (PSSA) that focused on protecting maritime environment at the same time allowing shipping industry to continue without much interruptions. This piece of research will concentrate on the effects on maritime traffic within the aspects of marine life in the wake of proclaiming MPAs by States, with special attention to the proposals on shifting of traffic lanes for their survival. A Case Study will also be conducted in relation to the Cetaceans in the Southern Indian Ocean belt off Sri Lanka facing imminent threat of collisions with ships in searching for a balance between development and the environmental protection.